A qualitative assessment of hydrogen generation techniques for fuel cell applications - Chaudhary K.; Bhardvaj K.; Chaudhary A. (My University, 2025)
Meeting energy demands necessitates the initial focus on hydrogen generation, followed by prioritizing hydrogen storage and transportation. Hydrogen generation can be categorized into on-site and off-site methods. Opting for on-site hydrogen generation is preferable when powering fuel cells for electricity generation, as it eliminates the costs associated with storage and transportation. Nevertheless, certain off-site hydrogen production techniques coupled with storage and transportation are more cost-effective than some on-site generation approaches. In this review paper, diverse hydrogen production methods (both on-site and off-site) are explored, involving a range of chemical compounds such as composite materials, various photosynthetic bacteria, different electrolysis approaches for water, aluminum-assisted hydrolysis, and steam reforming of methane and methanol. The paper offers a thorough examination of the hydrogen generation method within its peer group, leading to conclusions that are drawn from their potential exergo-economic implications. Furthermore, the viability of different methods for generating hydrogen, particularly in the context of fuel cell applications, is indicated. © 2023 Elsevier Ltd